2009
DOI: 10.1159/000241672
|View full text |Cite
|
Sign up to set email alerts
|

Micropapillary Pattern in Urothelial Carcinoma: A Clinicopathological Analysis

Abstract: Objectives: Our aim was to review our pathological archive to find out the actual incidence of micropapillary pattern (MPP) in our urothelial carcinoma patient population and determine its correlation with clinical outcome. Patients and Methods: 14 out of 170 cases with complete clinical follow-up were clinicopathologically analyzed. The extent of MPP was determined as tumor percentage. Results: 12 further cases with MPP were defined in the review. The percentage of patients with positive MPP increased in para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 31 publications
(12 reference statements)
0
14
0
3
Order By: Relevance
“…Tüm ürotelyal karsinomların %0,6'sını oluşturmaktadır. 26 Erken metastaz potansiyeli ve kötü prognozu nedeni ile ürotelyal karsinomdan patolojik ayrımının yapıl-ması önemlidir. Erkeklerde daha sık görülmekte-dir.…”
Section: Mi̇kropapi̇ller üRotelyal Karsi̇nomunclassified
“…Tüm ürotelyal karsinomların %0,6'sını oluşturmaktadır. 26 Erken metastaz potansiyeli ve kötü prognozu nedeni ile ürotelyal karsinomdan patolojik ayrımının yapıl-ması önemlidir. Erkeklerde daha sık görülmekte-dir.…”
Section: Mi̇kropapi̇ller üRotelyal Karsi̇nomunclassified
“…23 Prognostically, IMPC is recognized as an aggressive variant of urothelial carcinoma that is commonly associated with extensive lymphovascular invasion. 3,4,6,10,[12][13][14][15][16][17][18]22,23,24,34,35,37,38 In the largest reported series to date, IMPC had 5-year and 10-year KaplanMeier overall survival rates of 54% and 27%, respectively. 18 It has also been suggested that IMPC is predictive of a poor response to standard intravesical therapy relative to usual invasive urothelial carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Since that initial description, IMPC has become increasingly well recognized as a unique and aggressive variant within the genitourinary tract, 3,4,6,10,[12][13][14][15][16][17][18]22,23,24,34,35,37,38 and in other organs including the breast, lung, salivary gland, and colon. 7,28,29,36,40 Given the propensity for lymphovascular invasion and lymph node metastasis, frequent presentation with high-stage disease, and the reported poor response to standard intravesical therapy, some urologic oncologists have proposed early cystectomy for patients with a diagnosis of IMPC, even in the absence of muscularis propria invasion on initial biopsy or transurethral resection.…”
mentioning
confidence: 99%
“…Ein weiteres morphologisches Merkmal stellt die invertierte zelluläre Polarisation dar, bei welcher die apikale Membrandomäne der Tumorzellen nach außen gerichtet zum umgebenden Stroma zeigt [19]. Das MPC der Harnblase wird ebenfalls wie das PUC meist von einem konventionellen Urothelkarzinom begleitet, wobei der prozentuale Anteil der mikropapillären Morphologie am Gesamtpräparat mit dem Tumorstadium korreliert und als prognostischer Faktor diskutiert wird [10,20].…”
Section: Mikropapilläres Karzinom Der Harnblaseunclassified
“…Zur Klinik des MPC existieren mehrere Fallberichte oder retrospektive Studien [20,21,22]. Das größte Fallkollektiv wird von Kamat et al [9] beschrieben.…”
Section: Klinische Besonderheitenunclassified